2017
DOI: 10.1111/liv.13275
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of type 2 diabetes mellitus incidence in different phases of hepatitis B virus infection: A meta‐analysis

Abstract: This study suggests that hepatitis B virus infection is not an independent risk factor for type 2 diabetes mellitus, but the development of cirrhosis may increase the incidence of type 2 diabetes mellitus cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 40 publications
(116 reference statements)
6
9
0
Order By: Relevance
“…To compare the effect of different statins on diabetic patients for the risk of cancers directly and indirectly, ORs were calculated by employing frequentist techniques, which were performed in the form of graph. A network plot, inconsistency plot, predictive interval plot, comparison-adjusted funnel plot, and rank diagram of respective statin types were applied using NMA tool as described in published article [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…To compare the effect of different statins on diabetic patients for the risk of cancers directly and indirectly, ORs were calculated by employing frequentist techniques, which were performed in the form of graph. A network plot, inconsistency plot, predictive interval plot, comparison-adjusted funnel plot, and rank diagram of respective statin types were applied using NMA tool as described in published article [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, considerable attention has been paid to hepatitis viruses, especially hepatitis B virus (HBV) and hepatitis C virus (HCV), as well as their extrahepatic effects on glucose metabolism. Results from the non‐transplant population suggested a notable association between HCV infection and diabetes, but the association between HBV infection and diabetes remained controversial . However, in a transplant setting, especially in KTRs, consensus regarding the association between hepatitis virus infection and diabetes is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Results from the non-transplant population suggested a notable association between HCV infection and diabetes, [8][9][10] but the association between HBV infection and diabetes remained controversial. [11][12][13][14][15] However, in a transplant setting, especially in KTRs, consensus regarding the association between hepatitis virus infection and diabetes is lacking. In the past three decades, although the prevalence of HBV and HCV infection among KTRs has declined significantly due to the universal implementation of precaution and HBV vaccination, up to 7% to 15% of KTRs are still infected with HBV, 16 and 10% are still infected with HCV.…”
Section: Introductionmentioning
confidence: 99%
“…17 The development of cirrhosis may increase the incidence of DM. [7][8][9][10]17 In addition, it is proposed that this is the rst study to indicate that the abnormal glucose metabolism rate was higher in CHB patients who were HBeAg negative, with IGR and DM prevalence rates of 31.94% and 34.72% in patients who were HBeAg negative in comparison to 17.39% and 21.74% in patients who were HBeAg positive. Previous studies suggested that the HBsAg status could in uence glucose metabolism, and maternal HBsAg carriers were an independent risk factor for gestational diabetes mellitus (GDM).…”
Section: Discussionmentioning
confidence: 91%
“…2 China is one of the HBV middle-and low-endemic areas worldwide,and approximately 93 million people are infected with HBV; among them, 20 million present with CHB. 1,3 Although the relationship between hepatitis B virus infection and diabetes mellitus (DM) remains controversial, several studies have shown that the prevalence rate of DM is signi cantly higher in the HBVinfected population, [4][5][6][7][8][9][10][11] particularly in those with high viral load, with a long duration of CHB, with cirrhosis, 4,6,7−10 or of Asian American race. 8 Our previous study has shown that 59.09% of CHB patients had high homeostasis model assessment of insulin resistance (HOMA-IR) values and 93.64% of individuals had low homeostasis model assessment of β cell function (HOMA-β) values.…”
Section: Introductionmentioning
confidence: 99%